Vat-based photopolymerization 3D printing: From materials to topical and transdermal applications - Angélica Graça; Sara Bom; Ana M. Martins; Helena M. Ribeiro; Joana Marto (Elsevier, 2024)
Three-dimensional (3D) printing is an innovative manufacturing method with the potential to revolutionize topical and transdermal dosage forms. Nowadays, it is established that Vat-based photopolymerization (VP) 3D printing technologies offer superior printing efficiency and versatility compared to other 3D printing technologies available on the market. However, there are some limitations that impair their full application in pharmaceutical contexts, such as the lack of a range of biocompatible materials for topical and transdermal applications. This review article explores all types of VP-based 3D printing and discusses the relevance of implementing this kind of technology. We start with a detailed description of the printing process, focusing on the commercial materials available and lab-made resins proposed by different authors. We also review recent studies in this field, which mainly focus on the fabrication of transdermal devices based on microneedle arrays. In the future, it is expected that the manufacturers of 3D printers invest in modifications to the printing apparatus to allow the simultaneous printing of different resins and/or compound types, which will open frontiers to the personalization of treatment approaches.